Age, sex, endurance capacity, and chronic heart failure affect central and peripheral factors of oxygen uptake measured by non-invasive and continuous technologies: support of pioneer work using invasive or non-continuous measures - Brochhagen, Joana; Coll Barroso, Michael T.; Baumgart, Christian; Wasmus, Daniel T.; Freiwald, Jürgen; Hoppe, Matthias W. (Frontiers in Sports and Active Living, 2023)
Introduction It is known that maximum oxygen uptake depends on age, sex, endurance capacity, and chronic heart failure. However, due to the required invasive or often applied non-continuous approaches, less is known on underlying central and peripheral factors. Thus, this study aimed to investigate the effects of age, sex, endurance capacity, and chronic heart failure on non-invasively and continuously measured central and peripheral factors of oxygen uptake. Methods 15 male children (11 ± 1 years), 15 male (24 ± 3 years) and 14 female recreationally active adults (23 ± 2 years), 12 male highly trained endurance athletes (24 ± 3 years), and 10 male elders (59 ± 6 years) and 10 chronic heart failure patients (62 ± 7 years) were tested during a cardiopulmonary exercise test on a cycling ergometer until exhaustion for: blood pressure, heart rate, stroke volume, cardiac output, cardiac power output, vastus lateralis muscle oxygen saturation, and (calculated) arterio-venous oxygen difference. For the non-invasive and continuous measurement of stroke volume and muscle oxygen saturation, bioreactance analysis and near-infrared spectroscopy were used, respectively. A two-factor repeated measure ANOVA and partial eta-squared effect sizes (ηp2) were applied for statistical analyses at rest, 80, and 100% of oxygen uptake. Results For the age effect, there were statistically significant group differences for all factors (p ≤ .033; ηp2≥.169). Concerning sex, there were group differences for all factors (p ≤ .010; ηp2≥.223), except diastolic blood pressure and heart rate (p ≥ .698; ηp2≤.006). For the effect of endurance capacity, there were no group differences for any of the factors (p ≥ .065; ηp2≤.129). Regarding chronic heart failure, there were group differences for the heart rate and arterio-venous oxygen difference (p ≤ .037; ηp2≥.220). Discussion Age, sex, endurance capacity, and chronic heart failure affect central and peripheral factors of oxygen uptake measured by non-invasive and continuous technologies. Since most of our findings support pioneer work using invasive or non-continuous measures, the validity of our applied technologies is indirectly confirmed. Our outcomes allow direct comparison between different groups serving as reference data and framework for subsequent studies in sport science and medicine aiming to optimise diagnostics and interventions in athletes and patients.